Efektivitas Video Project-Based Learning terhadap Level Kebugaran Jasmani dan Status Gizi - Nugroho, Wildan Alfia (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
This research aims to examine the effect of Video Project-Based Learning on the Physical Fitness Level and Nutritional Status of MKDU Physical Education and Sports Students at the Indonesian Education University. The research method uses an experimental pretest-posttest group design. The sample in this study was students from the Indonesian University of Education who took part in MKDU Physical Education and Sports with an age range of 18-22 years, totaling 37 students. The sampling technique used was cluster random sampling. The research instruments used were the Cooper Test to determine fitness level and BMI to measure nutritional status. Data analysis used the Paired Sample T-Test and the N-Gain Score test with SPSS version 21 software. The research results showed a significant increase in the VO2Max value between the pre-test and post-test results with Sig. 0.000 < 0.005. Meanwhile, the average BMI value is 20.5, including the normal category. The N-Gain Score test for VO2Max is 0.22 with a moderate level of effectiveness. Project-Based Learning videos have been proven to have a significant effect on physical fitness and nutritional status.